Agro-Fruit-Forest Systems Based on Argan Tree in Morocco: A Review of Recent Results - Chakhchar, Abdelghani; Ben Salah, Imane; El Kharrassi, Youssef; Filali-Maltouf, Abdelkarim; El Modafar, Cherkaoui; Lamaoui, Mouna (Frontiers in Plant Science, 2022)
The argan tree, Argania spinosa (L.) Skeels, is a horticultural forestry species characterized by its endemicity and adaptation to arid and semi-arid zones in the southwest of Morocco. Despite its limited geographical distribution, argan tree presents large genetic diversity, suggesting that improvement of argan is possible. This species plays important ecological, and socioeconomic roles in the sustainable development of the country. The integration of arganiculture into Moroccan agricultural policy has been implemented through a sector strategy, which is fully aligned with the conservation and regeneration of argan forest. A. spinosa is suitable for incorporation into different agroforestry productive systems under agro-fruit-forest model and its domestication will provide a powerful means of socio-economic and environmental management. Here, we provide an overview of the argan tree literature and highlight the specific aspects of argan stands, as agro-forest systems, with the aim of developing an adequate strategy of conservation and domestication of this species. We introduce promising programs and projects for argan plantations and arganiculture, which have been adopted to relieve anthropogenic pressure on the natural argan forest.